Kajian Strategi Pemasaran Obyek Wisata Gunung Kawi Tampaksiring Kabupaten Gianyar Ditinjau dari Persepsi Wisatawan - I Made Astrama; I Gede Aryana Mahayasa (Widya Manajemen, 2021)
The purpose of this research is to study the marketing strategy model of the Gunung Kawi Cliff Temple in Tampaksiring. The main target of tourism development must be to improve the welfare of the community, especially the people of Tampaksiring Gianyar. Respondents were 74 tourists. The research was conducted by sampling. This study uses descriptive analysis to determine inferential by evaluating the measurement model (outer model) and the structural model (structural model / inner model). The results show that the attributes of tourism objects have a positive and significant effect on the image, the promotion has a significant effect on the image, and individual characteristics have a positive and significant effect on the image, but the image itself has a positive and significant influence on the decision of tourists to visit tourist objects. Tebing Gunung Kawi Temple, Tampasiring.